2018
DOI: 10.4103/0366-6999.233655
|View full text |Cite
|
Sign up to set email alerts
|

Five Years' Outcomes of Trabeculectomy with Cross-linked Sodium Hyaluronate Gel Implantation for Chinese Glaucoma Patients

Abstract: Background:Trabeculectomy is the most efficient surgical treatment. Prevention failure of bleb cicatrix would lead to unsatisfactory postoperative intraocular pressure (IOP) controlling and unsatisfactory success rate. The aim of this study was to evaluate the 5-year outcomes of trabeculectomy with a cross-linked sodium hyaluronate gel implantation for Chinese glaucoma patients.Methods:This is a prospective, case-controlled study. Patients who were to be applied first-time trabeculectomy in the Department of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To obtain hydrogel from HA, the latter might be crosslinked by chemical modification. In addition to creating a three-dimensional structure, chemical modification makes it possible to achieve better physicochemical characteristics in hydrogels, thereby increasing their resistance to biodegradation [ 131 ].…”
Section: Degradable Propertiesmentioning
confidence: 99%
“…To obtain hydrogel from HA, the latter might be crosslinked by chemical modification. In addition to creating a three-dimensional structure, chemical modification makes it possible to achieve better physicochemical characteristics in hydrogels, thereby increasing their resistance to biodegradation [ 131 ].…”
Section: Degradable Propertiesmentioning
confidence: 99%
“…stated that by 5 years 78% patients had postoperative IOP below 21 mmHg with sodium hyaluronate and 54% reached the goal in the group with only trabeculectomy. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ologen is a biodegradable three-dimensional collagen-glycosaminoglycan copolymer matrix implant that may also act as a physical spacer [ 56 ]. In an RCT, Ologen was shown to improve IOP control and blunt the hypertensive phase in Ahmed glaucoma valve surgery immediately after surgery but not at 6 or 12 months post-surgery [ 184 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%
“…In an RCT, Ologen was shown to improve IOP control and blunt the hypertensive phase in Ahmed glaucoma valve surgery immediately after surgery but not at 6 or 12 months post-surgery [ 184 ]. Although early clinical studies comparing the rates of complications and efficacy of Ologen to MMC in trabeculectomy showed mixed results, recent trials have shown the comparable or superior efficacy of Ologen [ 56 ]. When comparing Ologen and perfluoropropane in trabeculectomy, the IOP values were similar in the first 12 months of follow-up, but the Ologen group showed a more significant reduction in IOP during the last 24 months of follow-up [ 50 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%